2022
DOI: 10.1155/2022/1345006
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological-Based Validation of Polyalthia suberosa Leaf Extract in Neurological, Hyperalgesic, and Hyperactive Gut Disorders Using Animal Models

Abstract: Polyalthia suberosa (Roxb.) is a plant used to cure coughs, dysentery, fevers, joint aches, rheumatic pain, inflammation, and a variety of skin diseases. The aim of the study was to evaluate the ethyl acetate extract of Polyalthia suberosa (P. suberosa) leaves and their effects on mice for neuropharmacological, analgesic, and antidiarrheal activities. For neurological studies, the hole cross, hole board, open field, and thiopental sodium-induced sleep duration measurement methodologies were used. The castor oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…NH 3 solution (25 percent) and fltered. Te needed pure chemical was obtained using benzene recrystallization (II) [18][19][20].…”
Section: General Methods For the Synthesis Of 2-amino-benzo-mentioning
confidence: 99%
“…NH 3 solution (25 percent) and fltered. Te needed pure chemical was obtained using benzene recrystallization (II) [18][19][20].…”
Section: General Methods For the Synthesis Of 2-amino-benzo-mentioning
confidence: 99%
“…Fruits of P. suberosa have been used as anti-diarrheal. The leaves have been used to treat colds and coughs, and the barks have been used as analgesic [9]. Reported biological activities include antioxidant, anti-inflammatory, anticancer, antibacterial, and antiviral [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Thwaites is an evergreen shrub traditionally used as laxative, abortifacient, analgesic, and in treatment of numerous skin infections. It was reported that different extracts of P. suberosa exerted anti-inflammatory, analgesic, anti-bacterial, antioxidant, and neuropharmacological activities [9,10]. Despite the biological importance of this plant, the isolated essential oil from the leaves wasn't fully investigated, only the cytotoxic and antimicrobial activities have been studied [12].…”
Section: Introductionmentioning
confidence: 99%